L1 Antisense Promoter Drives Tissue-Specific Transcription of Human Genes. (9th May 2006) - Mätlik, Kert; Redik, Kaja; Speek, Mart
Abstract : Transcription of transposable elements interspersed in the genome is controlled by complex interactions between their regulatory elements and host factors. However, the same regulatory elements may be occasionally used for the transcription of host genes. One such example is the human L1 retrotransposon, which contains an antisense promoter (ASP) driving transcription into adjacent genes yielding chimeric transcripts. We have characterized 49 chimeric mRNAs corresponding to sense and antisense strands of human genes. Here we show that L1 ASP is capable of functioning as an alternative promoter, giving rise to a chimeric transcript whose coding region is identical to the ORF of mRNA of the following genes: KIAA1797, CLCN5, and SLCO1A2 . Furthermore, in these cases the activity of L1 ASP is tissue-specific and may expand the expression pattern of the respective gene. The activity of L1 ASP is tissue-specific also in cases where L1 ASP produces antisense RNAs complementary to COL11A1 and BOLL mRNAs. Simultaneous assessment of the activity of L1 ASPs in multiple loci revealed the presence of L1 ASP-derived transcripts in all human tissues examined. We also demonstrate that L1 ASP can act as a promoter in vivo and predict that it has a heterogeneous transcription initiation site. Our data suggest that L1 ASP-driven transcription may increase the transcriptional flexibility of several human genes.